ANALYSIS OF THE NATIONAL PRACTICE OF IMPROVING THE EFFICIENCY OF THE SMALL BUSINESS DEVELOPMENT MARKET INFRASTRUCTURE IN THE USA (International Congress on Economics, Management and Business Studies, 2026)
The article analyzes the practice of the United States, which is a leader in innovative activity in improving the efficiency of the market infrastructure for the development of small businesses, identifies the national characteristics of the country. At the same time, it assesses the possibilities of creative use of the experience formed in the US practice in the conditions of Uzbekistan.
Keywords: entrepreneurship, small business, small business potential, active business, market infrastructure, small business activities, business environment